PAKISTAN'S GEOSTRATEGIC POSITION AND ITS IMPACT ON MIDDLE EASTERN POLITICS - Dr.Farhana Kousar; Gul Muhammad Behan; Shazli (Journal of Religion and Society, 2025)
Pakistan's geostrategic location has long made it a pivotal player in global and regional politics, especially in the context of the Middle East. Situated at the crossroads of South Asia, Central Asia, and the Middle East, Pakistan holds significant military, economic, and political leverage. Its proximity to key Middle Eastern countries such as Saudi Arabia, Iran, and Afghanistan places it at the heart of ongoing geopolitical dynamics. Pakistan's role as a key ally of both the United States and China, coupled with its close ties to the Gulf states, has also shaped its influence in Middle Eastern politics. The nation's involvement in regional security matters, particularly with regard to Afghanistan and the ongoing tensions between Iran and Saudi Arabia, has deepened its strategic significance. Pakistan's military strength, nuclear capabilities, and its participation in international coalitions further reinforce its status as a key actor in the region. Additionally, Pakistan's role in mediating conflicts, managing refugees, and balancing its relations between Western powers and Middle Eastern countries has allowed it to maintain a unique diplomatic position. This paper examines the various dimensions of Pakistan's geostrategic position and its implications for Middle Eastern politics, exploring the impact of its alliances, military engagement, and diplomatic initiatives in shaping the region's future. Keywords: Pakistan, Geostrategic Position, Middle East, Geopolitical Dynamics, Regional Politics, Saudi Arabia, Iran, Afghanistan, Diplomacy, Military Alliances